PURCHASE DECISION EFFECTS OF IN STORE LIVE STREAMING IN INDONESIA - Kurnia Chris Pradana Wicaksono; Denise Theresia Laurena; Annisa Fathurrohmah; Junnany; Ronald Octavianus (Jurnal Pijar, 2024)
Introduction- Based on previous literature, in-store live streaming has gained immense popularity in the Chinese market, providing interactive engagement for consumers. This study investigates how in-store live streaming influences Indonesian consumers' desire to make in-person purchases, considering different retail environments and influencer characteristics in the Indonesian market. In this research, we add the variable of Consumers Attitude toward Platform Interactivity, in addition to the previous two variables, Consumers Attitude toward In-Store Influencer and Consumers Attitude toward Product in the organism in the SOR model. Review of Literature and Hypotheses Development- The present research employs the Stimulus-Organism-Response (SOR) model to examine the influences of informativeness, wishful identification, para-social interaction, and customer inspiration on consumers’ perceptions of influencers, products, and platform interactivity. Research Method-. This research examines how in-store live streaming influences consumers' offline purchase intent in Indonesia. A survey of 300 live stream viewers measured perceptions of the influencer, product, and platform, along with offline purchase motivation. Findings from exploratory factor and regression analysis reveal that an informative, interactive, and inspiring streaming session positively affects attitudes and buying intent. Results and Discussion- The majority of respondents were 26-35 year old employed females with an undergraduate degree and monthly income below IDR 16 million. Shopee (38%) and TikTok (37%) were the most used platforms for viewing live streams. Exploratory factor analysis confirmed scale validity and reliability. Regression analysis revealed informative and inspirational streaming content positively influences attitudes towards the influencer and product, driving key purchase motivation. An engaging platform also reinforces buying intent. These findings indicate live commerce can effectively stimulate offline sales in Indonesia. Conclusion- The research examines the impact of in-store live streaming on consumer purchase decisions in Indonesia. Results reveal a positive relationship between informativeness, wishful identification, para-social interaction, and inspiration with attitudes toward influencers, products, and platforms. Positive perceptions of influencers and products lead to increased offline purchase intent after live streaming. Moreover, interactive platforms contribute to motivating offline purchases. Implementing an effective in-store live streaming strategy can effectively enhance offline purchase intentions.